2008
DOI: 10.1111/j.1467-9450.2008.00645.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the premenstrual syndrome on facial expressions of sadness

Abstract: The PMS group experienced various visual stimuli in a more depressed way during the luteal phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
1
0
0
Order By: Relevance
“…It remains unclear whether the unexpected findings in the depressor muscle site in the present study are due to the young age of our participants or results from more general methodological issues in the adult literature. Notably, the lack of muscular activity involved in pulling the corners of the mouth is in agreement with other EMG studies that have failed to show increases in depressor activity following sad stimuli (Mass et al, 2008;Oberman et al, 2009;Schwartz et al, 1976). Future studies should reconsider recording activation in the depressor muscle, even more since our results suggest that a differentiation between mimicry in response to negative emotional facial expressions can also be made when recording a combination of corrugator and frontalis activity.…”
Section: Discussionsupporting
confidence: 91%
“…It remains unclear whether the unexpected findings in the depressor muscle site in the present study are due to the young age of our participants or results from more general methodological issues in the adult literature. Notably, the lack of muscular activity involved in pulling the corners of the mouth is in agreement with other EMG studies that have failed to show increases in depressor activity following sad stimuli (Mass et al, 2008;Oberman et al, 2009;Schwartz et al, 1976). Future studies should reconsider recording activation in the depressor muscle, even more since our results suggest that a differentiation between mimicry in response to negative emotional facial expressions can also be made when recording a combination of corrugator and frontalis activity.…”
Section: Discussionsupporting
confidence: 91%
“…One study found people with PMS symptoms produced more sad facial expressions when viewing emotionally charged stimuli during the luteal phase. 37 Another study asked people about their experience of negative, positive, and neutral life events over different timelines (ranging from the past month to the past 3 years). 38 When tested in the late-follicular phase, PMS symptoms were positively associated with reporting more negative life events and less positive life events.…”
Section: Discussionmentioning
confidence: 99%